PEMBUATAN APLIKASI GAME MERAWAT HEWAN PELIHARAAN DENGAN MENGGUNAKAN MACROMEDIA FLASH 8.0 - Aris Syafrando; Jusuf Wahyudi; Yode Arliando (UNIVED Press, 2014)
Game is one of the major industries in the world today. The development of the game at this time is very fast with a variety of types, ranging from games that can only be played by one person only to be played by several people at once. Flash is a powerful program to create gaming applications, both for desktop (computer) and mobile phones. In a computer or other devices would not be complete if it did not have the game. Making games can be done in various ways. In making a game using flash then the process of drawing the characters, backgrounds, sound effects and animation support can be done with this software. In the manufacture of pet care for this game, the elements used in the form of characters, back-grounds and other elements is to use the tools that are available in flash and can also prepare the music and sound effects. Elements that have been compiled and made then arranged in scenes, layers and frames in accordance with what was designed. In flash action script to set also contained the elements of caring pet in this game so that it becomes more interesting to play.Key words: Flash, Game Play.